WE INTER-ARE: THE PANDEMIC CHALLENGE REDEFINING HUMANS AND COMMUNITIES - K. Abraham (Acta Theologica)
The COVID-19 pandemic calls for a critical introspection into our way of being human in relation to other forms of life on this planet. Given that social hierarchies attribute higher and lower status to human beings based on their race, class, caste and gender identity, and legitimise the exploitation of other human beings and the earth, re-thinking our hierarchical positioning as “masters” of this universe becomes imperative. In this context, ecofeminist reconstruction of relationality is projected as a corrective, as it focuses on linking relationships instead of ranking relationships. In addition, the mystical notion “We Inter-Are”, shared by the visionary Buddhist sage Thich Nhat Hanh, is proposed as a key for growing into a consciousness of inter-relationality with other beings on this planet, as it opens us to the infinite mystery of the deeper relatedness of all forms of life. Viewed from this perspective, the pandemic can become a defining moment in the evolutionary story of human beings.